The Effect of Service Quality and Price on Purchasing Decision of Telkomsel Internet Services In Indonesia - Priyatna, Inayah Kamilah; Marsudi, Marsudi; Rahadjeng, Erna Retna (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The purpose of this research is to examine and analyze the effect of service quality and price on purchasing decisions for Telkomsel mobile internet services in Indonesia. The population used in this study were consumers who chose and used Telkomsel cellular internet services in the last month with a sample size of 105 respondents. This study uses quantitative research using a questionnaire. The analysis technique used is multiple linear regression analysis. The results of this study indicate that service quality has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. As well as the quality of service and price have a simultaneous and significant effect on the quality of purchases with the dominant influence of the price variable.